Outcomes of conventional transarterial chemoembolization for hepatocellular carcinoma ≥10 cm. Issue 7 (21st May 2019) - Miyayama, Shiro; Kikuchi, Yuzo; Yoshida, Masanori; Yamashiro, Masashi; Sugimori, Natsuki; Ikeda, Rie; Okimura, Kotaro; Sakuragawa, Naoko; Ueda, Teruyuki; Sanada, Taku; Watanabe, Hiroyuki; Notsumata, Kazuo
Abstract : Aim: To retrospectively evaluate the outcomes of conventional transarterial chemoembolization (cTACE) for hepatocellular carcinoma (HCC) ≥10 cm. Methods: Twenty‐five patients with naïve HCC ≥10 cm (mean maximum tumor diameter, 130 ± 27.6 mm; single [ n  = 12], 2–9 [ n  = 6], and ≥10 [ n  = 7]) without extrahepatic spread treated with cTACE were eligible. Five (20%) had vascular invasion. Two to three stepwise cTACE sessions using iodized oil ≤10 mL in one cTACE session were scheduled. When the tumor recurred, additional cTACE was repeated on demand, if possible. Overall survival (OS) rates were calculated using the Kaplan–Meier method. The prognostic factors were evaluated using uni‐ and multivariate analyses. Results: Stepwise cTACE sessions were completed for 20 (80%) patients, but could not be completed for four (16%). In the remaining (4%) patient, the whole tumor was embolized in one session. Additional treatment, mainly cTACE, was undertaken for 19 (76%) patients. The OS rates at 1, 3, and 5 years were 68, 34.7, and 23.1%, respectively. A tumor number of three was a significant prognostic factor ( P  = 0.020) and the 1‐, 3‐, and 4‐year OS rates in patients with ≤3 and ≥4 tumors were 81.3 and 33.3, 55.6 and 11.1, and 38.9% and 0%, respectively. Whole tumor embolization and the serum level of protein induced by vitamin K absence or antagonist‐II were also significant prognostic factors ( P  < 0.001 and P  = 0.042, respectively). Bile duct complications requiring additional interventions developed in two (8%) patients. Conclusion: Conventional TACE is safe and effective for huge HCCs, but has limited effects in cases with four or more tumors.